Visualizing Alternative Phosphorus Scenarios for Future Food Security - Neset, Tina-Simone; Cordell, Dana; Mohr, Steve; VanRiper, Froggi; White, Stuart (Frontiers in Nutrition, 2016)
The impact of global phosphorus scarcity on food security has increasingly been the focus of scientific studies over the past decade. However, systematic analyses of alternative futures for phosphorus supply and demand throughout the food system are still rare and provide limited inclusion of key stakeholders. Addressing global phosphorus scarcity requires an integrated approach exploring potential demand reduction as well as recycling opportunities. This implies recovering phosphorus from multiple sources, such as food waste, manure, and excreta, as well as exploring novel opportunities to reduce the long-term demand for phosphorus in food production such as changing diets. Presently, there is a lack of stakeholder and scientific consensus around priority measures. To therefore enable exploration of multiple pathways and facilitate a stakeholder dialog on the technical, behavioral, and institutional changes required to meet long-term future phosphorus demand, this paper introduces an interactive web-based tool, designed for visualizing global phosphorus scenarios in real time. The interactive global phosphorus scenario tool builds on several demand and supply side measures that can be selected and manipulated interactively by the user. It provides a platform to facilitate stakeholder dialog to plan for a soft landing and identify a suite of concrete priority options, such as investing in agricultural phosphorus use efficiency, or renewable fertilizers derived from phosphorus recovered from wastewater and food waste, to determine how phosphorus demand to meet future food security could be attained on a global scale in 2040 and 2070. This paper presents four example scenarios, including (1) the potential of full recovery of human excreta, (2) the challenge of a potential increase in non-food phosphorus demand, (3) the potential of decreased animal product consumption, and (4) the potential decrease in phosphorus demand from increased efficiency and yield gains in crop and livestock systems.